Effect of clinical pharmacist encounters in the transitional care clinic on 30-day re-admissions: A retrospective study - Panid Borhanjoo; Priscile Kouamo; Mafuzur Rahman; Margaret Norton; Madhavi Gavini (AIMS Press, 2019)
Hospitalized patients who meet specific criteria at discharge are referred to the transitional care clinic team consisting of a nurse practitioner and/or physician and a clinical pharmacist. In collaboration with the providers, the pharmacist reviews medications for appropriateness, assesses adherence, recommends medication changes and provides education. The purpose of this study was to measure the effect of an outpatient transitional care clinical pharmacist on 30-day re-admissions in an urban setting serving a population of low socioeconomic status. After receiving IRB approval, this single-center retrospective study analyzed records of 573 patient visits of which nearly 75% included a clinical pharmacist interaction. Rates of 30-day re-admissions were not statistically different among the two groups, however, it was found that each added co-morbidity significantly increased the patients' 30-day re-admission rate by 26%.